A Mechanism-Based Population Pharmacokinetic Analysis Assessing the Feasibility of Efavirenz Dose Reduction to 400 mg in Pregnant Women - Stein Schalkwijk (2018)
© 2018 The Author(s) Background: Reducing the dose of efavirenz can improve safety, reduce costs, and increase access for patients with HIV infection. According to the World Health Organization, a similar dosing strategy for all patient populations is desirable for universal roll-out; however, it remains unknown whether the 400 mg daily dose is adequate during pregnancy. Methods: We developed a mechanistic population pharmacokinetic model using pooled data from women included in seven studies (1968 samples, 774 collected during pregnancy). Total and free efavirenz exposure (AUC24and C12) were predicted for 400 (reduced) and 600 mg (standard) doses in both pregnant and non-pregnant women. Results: Using a 400 mg dose, the median efavirenz total AUC24and C12during the third trimester of pregnancy were 91 and 87% of values among non-pregnant women, respectively. Furthermore, the median free efavirenz C12and AUC24were predicted to increase during pregnancy by 11 and 15%, respectively. Conclusions: It was predicted that reduced-dose efavirenz provides adequate exposure during pregnancy. These findings warrant prospective confirmation.